The implications of face mask wearing for babies and families during the COVID-19 pandemic: A discussion. (September 2022) - Staff, Mrs Lynette; Green, Janet; Bromley, Patricia; Jones, Linda; Petty, Julia
Abstract : COVID-19 has changed the way that newborn babies are cared for within the neonatal setting, and infants in the first year of their lives, due to the introduction of social distancing and the wearing of face masks to limit the spread of the infection. Potential implications of these practices exist, related to the normal development of attachment, face processing and recognition by the infant, and connections with others. This paper discusses the importance of face-to-face interactions in relation to these within the context of developmental theory. Mask wearing can potentially impact relational communication, requiring us to change our current ways of working. The possible implications of decreasing face-to-face interactions for the infant and relational communication are discussed, along with key recommendations for both parents and health professionals to mitigate the potential long-term effects on development related to human connection and attachment.